Case report: IgG4-related intracranial lesions mimicking multiple sclerosis in a 14-year-old girl - Qing, Pingying; Lu, Chenyang; Yan, Bing; Liu, Chang; Fox, David A.; Zhao, Yi; Liu, Yi; Tan, Chunyu (Frontiers in Neurology, 2022)
Objectives: IgG4-related disease (IgG4-RD) is distinguished by the infiltration of IgG4-positive plasma cells in a variety of tissues and organs. Even so, central nervous system lesions associated with IgG4-RD are scarce. We describe a case of IgG4-related brain parenchymal lesions that mimics multiple sclerosis in a young female. Methods: The patient was followed by our neurology and rheumatology teams. Clinical information was recorded and brain was screened using magnetic resonance imaging (MRI). During follow-up, we examined serum IgE and IgG4 and lymph node biopsy. Results: Here we have detailed a 14-year-old Chinese female suffering from diplopia, left eyelid ptosis, right facial numbness, and right lower limb weakness admitted to our institute. Brain MRI revealed multiple sclerosis-like lesions in brain parenchyma. During the follow-up, she developed lymphadenopathy. Elevation of serum IgG4 and IgE and lymph node biopsy favors a diagnosis of IgG4-RD. The patient had a good response to glucocorticoids and mycophenolate mofetil. Literature review summarized eight previously reported IgG4-RD involving brain parenchymal lesions. Discussion: Our case expands the known age spectrum of IgG4-RD. The intracranial IgG4-RD is rare and could mimics multiple sclerosis. Careful examination and dynamic review of disease history are crucial in the differential diagnosis.